Exposure to Endocrine Disrupting Chemicals and Male Reproductive Health - Jeng, Hueiwang Anna (Frontiers in Public Health, 2014)
Endocrine disrupting chemicals (EDCs) can interfere with normal hormonal balance and may exert adverse consequences on humans. The male reproductive system may be susceptible to the effects of such environmental toxicants. This review discusses the recent progress in scientific data mainly from epidemiology studies on the associations between EDCs and male reproductive health and our understanding of possible mechanisms associated with the effects of EDCs on male reproductive health. Finally, the review provides recommendations on future research to enhance our understanding of EDCs and male reproductive health. The review highlights the need for 1) well-defined longitudinal epidemiology studies, with appropriately designed exposure assessment to determine potential causal relationships; 2) chemical and biochemical approaches aimed at a better understanding of the mechanism of action of xenoestrogens with regard to low-dose effects, and assessment of identify genetic susceptibility factors associated with the risk of adverse effects following exposure to EDCs.